Estrous responses synchronized by a combination of PGF2a and GnRH hormones in Sapera goat. Issue 1 (June 2021) - Hafid A, A; Anggraeni, A; Pamungkas, F A; Sianturi, R G; Kusumaningrum, D A; Ishak, A B L; Mukhlisah, A N
Abstract: Estrous synchronization can uniformity of mating and kidding to a population of dairy goat females. The objective of this study was to evaluate response, duration and onset of estrous of Sapera does synchronized by PGF2α and PGF2α combined with GnRH hormones. Study used 16 Sapera does at the ages of one year old after reaching sexual maturity at average body weights of 26.52±2.51 kg (22.4—32.5 kg). Synchronization treatments were conducted for two different injections. Group one was injected two times of PGF2α within 11 day interval. While group two was injected by GnRH on the 9th day after the 1 st injection PGF2 α and before the 2 nd injection of this hormone within 11 day interval. Estrous observation was evaluated every three hours for four days after the 2 nd PGF2α injection. Estrous characteristics were based on behaviour and vulva condition of animals. The result revealed that the two groups of PGF2α vs PGF2 α + GnRH hormones gave significantly differences (P<0.05) to the responses of estrous (62.50 vs 100%), duration of estrous (18.75 hrs vs 33.75 hrs ) and onset of estrous (25.13 hrs vs 3.00 hrs). The conclusion was that PGF2α + GnRH combination presented more effective synchronization results as indicated by better response, duration and onset of estrous in Sapera goat.